FOSSIL REPTILES FROM THE PLEISTOCENE HOMO-BEARING LOCALITY OF BUIA (ERITREA, NORTHERN DANAKIL DEPRESSION) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The early to early-Middle Pleistocene fossil assemblage form the Buia area (Northern Danakil Depression, Eritrea) hosts, along with Homo and several other large mammal taxa, the following reptiles: Nile Crocodile, Crocodylus niloticus, Serrated Hinged Terrapin, Pelusios cf. P. sinuatus, Nile Monitor, Varanus niloticus and African Rock Python, Python gr. sebae. All the identified taxa belong to living species. At present, these taxa do not occur in the Northern Danakil depression since it is an arid area. P. sinuatus is not a member of the Eritrean herpetofauna. Although the marked preponderance of the crocodile remains is probably connected to the taphonomy of the sites and the collecting methods used, the ecological value of the reptile fauna corroborates that of the mammals, in indicating a lacustrine or fluvio-deltaic palaeoenvironment and a tropical/subtropical or even sub-Sahelic climate. The Buia remains represent the first reported Eritrean palaeoherpetofauna.